Legal framework and protection programs in Latin America and the Caribbean: challenges and opportunities in the protection of the rights of older adults - Castillo Aroca, Alberto (2024)
Introduction. This article provides a review of laws, regulations, and protection programs aimed at individuals over 60 years old in seven Latin American countries: Argentina, Bolivia, Chile, Colombia, Costa Rica, Mexico, and the Dominican Republic. Additionally, it examines the national and international regulations and agreements in which each of these countries participates. The main laws and protection programs for older adults in each mentioned countryare highlighted, with a focus on the aspects they address, particularly in terms of labor rights, access to healthcare, and housing. Method. documentary review of current national and international laws and conventions was conducted in each participating country. This analysis was carried out with a qualitative approach, aiming to identify areas for improvement and potential legal gaps in the protectionof the rights of older persons in these countries. Additionally, an examination was made on how these regulations address aspects related to economic security, healthcare, social participation, combating abuse and discrimination, labor rights, and access to housing. Results. The countries guarantee fundamental rights for older adults, including health, social security, housing, food, and social and culturalparticipation. However, disparities are observed in the presence of regulations and programs in specific areas. Conclusions. While the studied countries are signatories to the most important international conventions on the rights of older persons, and despite their progress in developing laws and regulations for their compliance, thisdoes not guarantee effective implementation. Therefore, further studies are needed to delve into the implementation aspect to identify possible gaps and challenges.